Egy dél-békési település, Mezőhegyes víz- és csatornaellátottságának vizsgálata 1990 és 2006 között - Zsótér, Brigitta (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The aim of the research was to find answer to the following question: did a small town (Mezőhegyes) in the southern part of County Békés manage to keep up with the other towns of the county in terms of sewerage in the period between 1990 and 2006? Regarding the length of the sewerage per one km of the public water network Mezőhegyes has never belonged to the towns with the best sewerage. It was the 12th on the list of twelve towns in 1990, the 7th on the list of seventeen in 2001, and in 2006 it was the 11th in the rank of eighteen towns. Considering the data of the sewerage it can be ascertained that Mező-hegyes could not reach even the average level of the towns in Békés from this point of view.